HISTORICAL REVIEW OF THE INSTITUTE OF APPEAL AND ITS DEVELOPMENT CHARACTERISTICS - Tsikhiseli, Nino (European Scientific Journal, ESJ, 2015)
The presented work - â€œHistorical Review of the Institute of Appeal and Its Development Characteristicsâ€ concerns the Appeal and its legal nature. The work is about the historical development and the establishment of appeal in various countries. In the work the following issues are defined: essence of Appeal, notion of Appeal and complete (unlimited) and incomplete (limited) types of Appeal.